BS EN 2713-012. Aerospace series. Cables, electrical, single and multicore for general purpose. Operating temperatures between – 55 °C and 200 °C. Part 012. MNA (1 core), MNB (pair), MNC (3 cores), MND (4 cores), cables family. Silver plated copper screened (spiral) and jacketed, UV laser printable. Product standard (11th November 2019) - British Standards Institution,
No abstract available